Lessons From Spider and Silkworm Silk Guts - Pérez-Rigueiro, José; Ruiz, Víctor; Cenis, José Luis; Elices, Manuel; Guinea, Gustavo Víctor (Frontiers in Materials, 2020)
The results presented in previous works on the formation of fibers from silkworm and spider silk guts are reviewed and new information is included on the glands that allow the formation of these fibers. Silk gut fibers are obtained directly from the silk glands by immersion in a mild acid solution and subsequent stretching. The fibers so produced were characterized in terms of their microstructure and mechanical properties. The comparison of silk gut fibers with their natural counterparts allows gaining new insights in the processing, microstructure and properties of both silkworm and spider silks.